Correlation between parental verbal violence behaviour and the aggressiveness of adolescents - Harmiardillah, Sylvi; Kusbiantoro, Dadang; Qowi, Nurul Hikmatul; Lestari, Trijati Puspita (Gaceta Médica de Caracas, 2022)
Introduction: The phenomenon of adolescents’ aggressive behaviour today has never subsided and even tends to increase. The factors causing the high incidence of quarrels are still unknown, but family quarrels and parental exposure to childhood abuse are predictors of aggressiveness among adolescents. This study aimed to examine the relationship between parents’ verbal violence behaviour and adolescents’ aggressive behaviour.